Scleroderma: considerations for dental hygienists - SL Tolle (Journal compilation 2008 Blackwell Munksgaard)
Scleroderma, the general name of a group of progressive diseases affecting the connective tissues is the most deadly of the varying connective tissue disorders. Characterized by abnormal thickening of the skin, this collagen-vascular disease is associated with immune dysfunction.